THE VALUE OF ARTS AND CULTURE: A CASE STUDY ON CREATIVE PLACEMAKING IN HIN BUS DEPOT, PENANG, MALAYSIA - Isa, Mohd Ismail; Shan, Ang Qiao (PLANNING MALAYSIA, 2024)
The arts and cultural sector are essential in sustaining George Town, Penang's UNESCO World Heritage Status. Creative placemaking incorporating the power of arts and culture can add value to the city's public space design. It involves revitalising abandoned public spaces to enhance neighbourhoods and strengthen local communities. This study aims to discover community participation and awareness in arts and culture. They are taking Hin Bus Depot, a creative hub in the heart of George Town, as the case study examines the impacts of creative placemaking projects on the community. In this context, creative placemaking is the approach that integrates arts and culture into a public space to enable transformation while also building character and quality of place. To test the hypothesis that arts and culture can positively impact the community, an online questionnaire survey was distributed to the locals and visitors of Penang. Respondents were asked about demographics, engagement, and awareness of arts and culture. The results showed the community's positive relationship with arts and culture and the success of Hin Bus Depot in bringing beneficial impact. The community's engagement in arts and culture has increased, contributing to the support of George Town's local arts scene. The concept of creative placemaking should be considered to promote better urban design in the future.